Trade Liberalization and Macro Economic Performance in Nigeria - Jude Chidi Onyenama (International Journal of Sustainability in Research, 2023)
This study examined trade liberalization and macro economic performance in Nigeria. The study made use of ordinary least square (OLS) for analysis using data from pen worth table (PWT) for the period of 1980-2016. The variables used in the analysis are (TOP) trade openness, (UNE) unemployment rate, (GDP) gross domestic product, (XR) exchange rate and (RINT) real interest rate. The result obtained indicates that Trade openness has an inconclusive relationship with the macroeconomic indicators in Nigeria. The implication is that GDP, RINT and UNE were negatively and positively related to Trade openness during the period of review respectively, going against the prior expectation. Hence the study recommends review of the degree of its trade liberalization by keeping trade openness rate below or at ceiling level in order to ensure an improved macro economic performance in Nigeria.